Structure and reactivities of rhenium and technetium bis-arene sandwich complexes [M(η6-arene)2]+. Issue 42 (2nd August 2017) - Meola, Giuseppe; Braband, Henrik; Jordi, Sara; Fox, Thomas; Blacque, Olivier; Spingler, Bernhard; Alberto, Roger
Abstract : Rhenium and 99 Tc bis-arene complexes for a molecule-based theranostic approach are presented. Conjugation of biovectors to benzene or substitution of naphthalene allows integration of {Re(η 6 -C6 H6 )} + in pharmaceutical lead structures. Abstract : Sandwich complexes are important building blocks in medicinal inorganic chemistry for group 6 and 8 elements but are almost unknown for the manganese triad. We present the syntheses and full characterization of the mixed-arene 99 Tc sandwich complexes [ 99 Tc(η 6 -hmbz)(η 6 -C6 H5 –NH3 )](PF6 )2 and [ 99 Tc(η 6 -hmbz)(η 6 -C6 H5 –Br)](PF6 ). Both comprise functionalities for conjugation to targeting molecules or for being included as substructures in pharmaceutically active lead compounds. Since η 6 -benzene ligands are too stably bound to be replaced with incoming ligands, we prepared naphthalene complexes [Re(η 6 -C6 H6 )(η 6 -napht)] + and [Re(η 6 -napht)2 ] + . Their reactivities towards substitution are increased and one or both naphthalene ligands can be replaced with mono- or multi-dentate ligands. Combining the features of 99 Tc and Re may lead to a molecule-based theranostic approach.